A Powerful Hydrogen‐Bond‐Donating Organocatalyst for the Enantioselective Intramolecular Oxa‐Michael Reaction of α, β‐Unsaturated Amides and Esters1. Issue 42 (27th August 2013) - Kobayashi, Yusuke; Taniguchi, Yamato; Hayama, Noboru; Inokuma, Tsubasa; Takemoto, Yoshiji
<x xml:space="preserve">Abstract</x> Tuning the organocatalyst: An unprecedented enantioselective intramolecular oxa‐Michael reaction of unactivated α, β‐unsaturated amides and esters catalyzed by a powerful hydrogen‐bond‐donating organocatalyst has been developed. Furthermore, the products obtained from this reaction have been used for the straightforward asymmetric synthesis of several natural products and biologically important compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>